Complex interplay of short- and long-chain branching on thermal and rheological properties of ethylene/α-olefin copolymers made by metallocene catalysts with oscillating ligand structure. (10th March 2017) - Ahmadi, Mostafa; Rezaei, Faezeh; Mortazavi, Seyed Mohammad Mahdi; Entezam, Mehdi; Stadler, Florian J.
Abstract: Unbridged oscillatory metallocenes are prone to produce heterogeneous chain microstructure, for instance, giving rise to elastomeric polypropylene. Here, we use the bis(2-phenylindenyl)ZrCl2 /MAO catalyst system, featuring oscillating ligands, to copolymerize ethylene with several α-olefins. Through investigation of chain microstructure, thermal and rheological properties, we show that the complex behavior of these materials can be justified by considering a catalyst with dual active center having different comonomer affinities. This behavior is consistent with the proposed mechanism of fast oscillating ligands, becoming locked upon proximity of cocatalyst counteranion, leading to diverse stereo- and comonomer selectivity. The unlocked, oscillating active center with lower comonomer response gives rise to mostly linear chains and is not affected by the presence of comonomer, while the locked one creates long chain branched chains, whose frequency decreases by introduction of comonomer. Copolymer samples exhibited bimodal MWD, dual crystallization mechanisms, and low frequency plateau modulus, specifically at higher comonomer levels. It was concluded that the overall behavior is determined by complex interplay of SCB and LCB, which leads to thermorheological complexity as well as phase separation. Graphical abstract: Oscillating metallocene catalyst is used in copolymerization of ethylene and several α-olefin comonomers. The dual nature of active centers leading to complex interplay of SCB and LCB is revealed by studying thermal and rheological properties. Highlights: Copolymerization of ethylene with several α-olefins using oscillatory metallocene. GPC and DSC results suggest a dual catalytic sites nature. Thermorheological complexity decreases at higher comonomer contents. A second plateau also appears at lower frequencies for higher comonomer contents. Locking/unlocking of the catalyst ligand can explain the observed behaviors.